Varredura fenotípica de nematoides C elegans mutantes para proteínas necessárias para a via de RNAi sistêmica - Camara, Henrique [UNIFESP] (2017)
Background and objective: SIDs and RSDs are proteins required for double stranded RNA transport in C. elegans. The mutants for their coding genes have tissue specific systemic RNAi defects. SID-2 is important for the incorporation of RNA from the environment to the organism, without a role in the transport of endogenous RNAs. RSD-3, RSD-2 e RSD-6 are specific for the transport to the germline, althought rsd-2 and rsd-6 mutants shows RNAi defects in the intestine. SID-1, SID-3 e SID-5 transport RNA to all non-neuronal tissues. Some of these proteins are conserved in more complex organisms, including humans, and assist the gene silencing produced by mobile RNAs. The mechanisms through which SIDs and RSDs mediate RNA transport are well described, but little is known about their roles in worm physiology. Therefore, the present work was conducted to identify physiological roles of SIDs and RSDs. Methods: We assessed the lifespan and age-related muscular function decline, oxidative and heat stress resistance, time of development and fertility in worms lacking functional SIDs and RSDs. Results: Systemic RNAi deficient worms reached adulthood, but the developmental time was delayed in sid-2, rsd-2, sid-1, sid-5 and sid-3 mutants. Mutations that impair RNA transport to the germline, with exception of sid-1, reduced brood size. In contrast, impaired systemic RNAi in somatic tissues, but not in the germline, rendered worms short-lived. Interestingly, the median lifespan was inversely correlated with the number of RNAi deficient somatic tissues (e.g. N2 = rsd-3 >rsd-2 > sid-1). The reduction in lifespan of some sid and rsd mutants was accompanied by premature age-related muscular dysfunction , assessed by reduced spontaneous contraction of the pharynx and the body-wall muscle, and reduced oxidative and heat stress resistance. Conclusions: Collectively, our data demonstrate that SIDs and RSDs are necessary in the germline for proper fertility. In different somatic tissues, but notably in the intestine, these proteins are necessary for normal development, longevity and stress resistance. This indicates that mobile RNAs are physiologically used as signaling molecules to control organismal homeostasis. These results provide insights into novel mechanisms of intertissue communication in multicellular organisms.